2013
DOI: 10.1136/jnnp-2012-304094
|View full text |Cite
|
Sign up to set email alerts
|

Brain atrophy and lesion load predict long term disability in multiple sclerosis

Abstract: This large multicentre study points to the complementary predictive value of atrophy and lesion volumes for predicting long term disability in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
264
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(291 citation statements)
references
References 41 publications
20
264
3
4
Order By: Relevance
“…The clinical disease course was well reflected in the rate of brain volume loss, which was most rapid in the severe subgroup who experienced ≥2 confirmed progressions and least rapid in the stable subgroup who experienced no confirmed progressions. These results confirm a relationship between brain volume loss and disability worsening in PPMS, consistent with findings in RMS 2, 3, 4, 5. The relationship between brain volume loss and disability worsening was sustained even in the absence of on‐study inflammatory activity, defined as new or enlarging T2 lesions or relapses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The clinical disease course was well reflected in the rate of brain volume loss, which was most rapid in the severe subgroup who experienced ≥2 confirmed progressions and least rapid in the stable subgroup who experienced no confirmed progressions. These results confirm a relationship between brain volume loss and disability worsening in PPMS, consistent with findings in RMS 2, 3, 4, 5. The relationship between brain volume loss and disability worsening was sustained even in the absence of on‐study inflammatory activity, defined as new or enlarging T2 lesions or relapses.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies in relapse‐onset multiple sclerosis (RMS) found a relationship between brain volume loss and disability worsening 2, 3, 4, 5. Moreover, patients with RMS and a small normalized brain volume are significantly more likely to worsen over 4 years than patients with large normalized brain volume but otherwise similar baseline characteristics 6.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Generally speaking, brain volume changes can be an important measure of tissue damage in patients with MS. 32 Indeed, baseline atrophy and high rates of subsequent volume loss are associated with cognitive impairment, fatigue and disability progression over the long term. 32,[35][36][37][38][39][40][41] In a complex disease such as MS, brain volume loss results from the sum of and interactions between various destructive pathological processes, 42 including irrever sible demyelination, and axonal and/or neuronal loss. The neurodegenerative pathology that occurs in MS is an important target for treatment; thus, MRI brain volume measures have been used in randomized clinical trials to monitor the effects of disease modifying thera pies on these parameters.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…1,2 Currently available disease-modifying therapies (DMTs) for relapsing-remitting MS (RRMS) modulate or suppress the immune system, reducing the risk for future inflammation and associated neurodegeneration. 3 Accordingly, the effect of DMTs on MRI-derived estimates of brain atrophy is a common outcome in MS trials.…”
mentioning
confidence: 99%